Manajemen Kemitraan Sekolah dengan Dunia Industri pada Kompetensi Keahlian Teknik Instalasi Tenaga Listrik di Sekolah Menengah Kejuruan Muhammadiyah 1 Klaten Utara - Gilang Isa Baskara; Tri Kuat; Muhammad Kunta Biddinika (Journal on Education, 2024)
Partnerships between Vocational High Schools (SMK) and the industrial world are vital in improving the quality of education and competency of graduates, however the existence of school partnership management should be paid attention to by educational institutions. This research aims to describe partnership management, including planning, organizing, implementing, and evaluating partnerships between SMK Muhammadiyah 1 North Klaten with competency in electrical power installation engineering expertise and the industrial world. This research uses a qualitative approach, data is obtained by observation, interviews, and documentation. The research results show that overall the management of school partnerships with industry has gone well, including (1) partnership planning, the school has carried out situation analysis and problem identification by paying attention to school goals so that several strategies for achieving goals are obtained, one of which is the implementation of the guest teacher program; (2) organizing partnerships is carried out by determining resources and activities to achieve school goals, namely by determining priority programs (guest teacher program), distributing tasks and authority, and coordinating with partners; (3) the implementation of partnerships between schools and industry is carried out through several activities in the form of curriculum alignment, internships, guest teacher programs, entrepreneurship training, and workforce recruitment; (4) partnership evaluation is carried out by measuring the implementation or results achieved compared to standards, improving competencies in the curriculum, both internally and externally by involving the industrial world.